The Crime of Murder against Parents by Children - Nurbaeti, Beti; Farhana, Farhana (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study aims to discover, analyze, and explain the factors that cause domestic violence among children. The method used in this paper is a normative juridical approach with laws and regulations sourced from primary legal materials, a conceptual approach sourced from secondary legal materials, and a case approach—data analysis using literature study techniques. This study indicates that the factors that cause domestic violence by biological children are family, personality, social, environmental, school/educational, social media, and economic factors. Or in detail, the factors that influence violence are family financial problems, jealousy problems, child problems, parent problems, sibling problems, politeness problems, and others.